PROBLEMATIKA PENDIDIKAN DALAM MENINGKATKAN KUALITAS PEMBELAJARAN PAI - Maghfirah Raihani; Setyo Supratno (Najah Bestari, 2026)
This research aims to identify and analyze the main problems inhibiting the improvement of Islamic Religious Education (PAI) learning quality. Using a qualitative method, it was found that the obstacles stem from three crucial dimensions: (1) Teachers: Limited competency in methodological innovation and technology utilization; (2) Curriculum: The gap between dense material and relevance to student needs in the modern era; and (3) Environment: Lack of interactive facilities and a suboptimal school environment for moral practice (akhlak laboratory). The conclusion indicates that improving PAI quality requires an integrated strategy through continuous professional development for teachers and curriculum reorientation to be more contextual and adaptive to the challenges of the 21st century. Keywords: : Educational Problems, Learning Quality, Islamic Religious Education (PAI), Teacher Innovation, Curriculum.